Babizna? Babcie jako bohaterki rodzimej prozy kobiet po 2010 roku - Pekaniec, Anna (Zagadnienia Rodzajów Literackich, 2022)
The text was conceived as a review, combined with an analysis and interpretation, of texts written by Polish women authors after 2010, especially novels and short story collections in which the grandmother is an important character. Women authors from the 1970s and 1980s, who in creating various herstories, make the eldest women in the family the disposers of narratives, responsible for building specific bridges between the past and the present, as well as the guardians of memory and guides through the labyrinth of interpersonal relations. The numerous representations of grandmothers in post-2010 literature is directly related to the ‘family turn’ in domestic prose announced over a decade ago, as well as to the transformations within women’s literature, in which the mother-daughter relationship is being replaced by a granddaughter (rarely grandson) — grandmother relationship. Granddaughters become narrators, through them the grandmothers’ stories taking verbal shape. The established bond enables the creation of alternative versions of herstories in which grandmothers, as delegates of the past, teach granddaughters in the present how to cope with the future. “The grandmotherly turn”, however, marks above all the emergence of the figure of the Polish grandmother, enabling granddaughters to speak about themselves (and them also) in their own voice.